Diabetic retinopathy in Down's syndrome. Issue 4 (1st April 1998) - Fulcher, Tim; Griffin, Margaret; Crowley, Seamus; Firth, Richard; Acheson, Robert; O'Meara, Niall
Abstract : AIM: To determine the prevalence of diabetic retinopathy in patients with Down's syndrome and diabetes mellitus. METHOD: Nine patients with Down's syndrome and diabetes mellitus were assessed. Factors recorded included type and duration of diabetes, level of diabetic control, blood pressure, urinalysis, and results of ophthalmological examination. RESULTS: The duration of diabetes ranged from 8 to 41 years (mean 17.6 years). All had satisfactory glycaemic control and blood pressure measurements on the low side of normal (mean 106.6/70 mm Hg). One patient had early background diabetic retinopathy. The remainder had no evidence of diabetic retinopathy. CONCLUSION: The low prevalence of diabetic retinopathy in these Down's syndrome patients, despite the long duration, is an interesting finding. It suggests some inherent protective factor against the development of diabetic retinopathy in this patient subgroup.